Newer Pedagogical Methods for Teaching and Learning in Pharmaceutical Education - Suryawanshi, Shailendra Sanjay; Palled, Mahesh; Maste, Meenaxi; Bhandurge, Parixit; Patil, Archana; Sharrannavar, Bhuvaneshwari; Bhandari, Ramesh; Bandekar, Siddhesh; Patil, Adarsh Arun (Indian Journal of Pharmaceutical Education and Research, 2026)
Pharmaceutical education has undergone a paradigm shift from traditional didactic instruction to more interactive, learner-centered approaches. This review explores modern pedagogical methods and presents real-world case studies demonstrating their application in pharmacy education. Lecture-based learning was shown to enhance foundational knowledge delivery, while inquiry-based and project-based strategies improved problem-solving and research aptitude. For instance, kinesthetic learning in medicinal chemistry practicals led to better retention of synthetic pathways, and game-based tools increased engagement in heterocyclic chemistry. Peer-assisted teaching boosted comprehension of molecular docking concepts, as reported through positive student feedback. Technology-driven tools like Molsoft enabled students to apply theoretical principles in drug-likeness prediction exercises. These methods, supported by qualitative observations and student performance reflections, collectively indicate improved engagement, critical thinking, and real-world readiness. The findings emphasize that integrating active learning, interdisciplinary collaboration, and hands-on activities can significantly enhance pharmaceutical education outcomes.
Keywords: Pharmaceutical Education; Active Learning; Pedagogical Innovation; Case-Based; Teaching; Problem-Solving Skills